Clinical Characteristics of Mother–Infant Dyad and Placental Pathology in COVID-19 Cases in Predominantly African American Population - Jani, Sanket; Jacques, Suzanne M; Qureshi, Faisal; Natarajan, Girija; Bajaj, Sujit; Velumula, Pradeep; Agu, Cindy; Bajaj, Monika (American Journal of Perinatology Reports, 2021)
Objective In this currently evolving coronavirus disease 2019 (COVID-19) pandemic, the evidence is scarce about the impact of COVID-19 infection on women in labor and neonates in an inner city African-Americans (AA) population. The objective of this study was to evaluate the clinical outcomes and placental pathology in mother–infant dyads in COVID-19 cases.Study Design Retrospective chart review was conducted on 34 COVID-19 positive mother–infant dyads to study their baseline characteristics and outcomes. Placental pathology was reviewed by two perinatal pathologists.Results COVID-19 was noted in 3% of pregnant women who delivered in our institution. The majority (82%) of them were asymptomatic. Out of the four mothers who were symptomatic, only three (9%) required supplemental oxygen. None of them required invasive ventilation. All the neonates tested negative for COVID-19 at 24 hours of age. There were no gross or microscopic pathological abnormalities detected that could be definitely associated with any COVID-19 related complications during pregnancy in any of the 34 placentas.Conclusion COVID-19 does not appear to increase morbidity and mortality among pregnant women and their neonates in a predominantly AA population. Our study did not find any evidence of vertical transmission of COVID-19 infection nor any specific findings on placental pathology.Key Points
Keywords: Covid-19; placenta pathology; vertical transmission; perinatal effect